2021
DOI: 10.1007/s00127-021-02152-3
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence due to common mental disorders in young employees in Sweden: are there differences in occupational class and employment sector?

Abstract: Background A large proportion of sickness absence (SA) in young adults is due to common mental disorders (CMDs). Still studies on CMD-related SA in young workers are lacking, especially studies for those employed in the private sector. The current study investigated the associations between sector of employment, occupational class and SA due to CMDs. In addition, associations between type of employment branch and SA due CMDs within each sector were examined. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…The prevalence of long-term SA (> 90 days) in the current study was higher among those employed in the private sector, primarily among those with previous depression/anxiety. This differs from findings reported earlier, where employees in the public sector were shown to have increased risk for long-term SA due to common mental disorders among young employees 7 or no difference between the sectors was observed at all in a sample of middle-aged employees 2 . Inconsistency in findings regarding long-term SA may be attributable to different features of study samples.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The prevalence of long-term SA (> 90 days) in the current study was higher among those employed in the private sector, primarily among those with previous depression/anxiety. This differs from findings reported earlier, where employees in the public sector were shown to have increased risk for long-term SA due to common mental disorders among young employees 7 or no difference between the sectors was observed at all in a sample of middle-aged employees 2 . Inconsistency in findings regarding long-term SA may be attributable to different features of study samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Young employees with a history of depression/anxiety were shown to have approximately the same risk for future SA in both private and public sectors. However, several previous studies reported higher SA rates in public than private sector in different age groups, with one explanation being that the difference in SA rates may be attributable to employee’s health 1 , 2 , 7 , 23 . Our findings of young employees suggest that depression/anxiety in early years may explain the different SA rates in public and private sectors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, it is worth mentioning that there were substantial differences in the absolute number of LMM days between the branches, with the highest number of LMM days in the health and social care branches among young individuals both with and without ADHD. Work disability, especially due to mental disorders, is a well-described problem in these branches, among others, due to work characteristics such as high job strain, effort–reward imbalances, and low job security [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. This suggests that the work environment that is specific for occupational branches affects individuals with and without ADHD to a similar extent.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, employees in the public sector have been shown to experience higher levels of stress, anxiety and depression when compared with private sector employees. 28 30 For example, in a large population-based cohort of young Swedish employees it was found that public sector workers had an elevated risk of sickness absence due to common mental disorders, compared with private sector employees. 30 Additionally, the cost associated with poor mental health seems to be disproportionally borne by the public sector in the form of absenteeism and presenteeism.…”
Section: Introductionmentioning
confidence: 99%